If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3*x = (1/6)*x // - (1/6)*x
3*x-((1/6)*x) = 0
3*x+(-1/6)*x = 0
17/6*x = 0 // : 17/6
x = 0
x = 0
| 3(x-10)+6=54 | | 6s+2=3+20 | | c-4/5=9 | | Tanx=20/13 | | 2040/24 | | A=R+ab | | 4a-9-5a=11 | | 9x-47=7(x-9) | | -54=3(7n-4) | | 10-(y+0.2)=6 | | 10+5(3w-2)=2w-13 | | 12x^5-60x^4=0 | | 2(u-5)=-9u+1 | | 2(u-5)=9u+1 | | ln(x-4)=2.18 | | (1/7)-(12/4-x^2) | | 15x^2-18x^2-25y+30= | | X^4=29 | | (x-4)=2.18 | | 4x+2y=10x-y=13 | | 2z+1=x+4 | | (1/7)-12/4-x^2 | | 9x^4+4x^2+5=15x^2+3 | | 12x^4-22x^2-4=0 | | 3x+2y=1x+8 | | 7v+19=5(v+5) | | 8X+9-3X=7X-8+7 | | 8X+9-3X=7X-8+7i | | 3[x+11]+5=68 | | 12x^2y-42x^2-4y+14=0 | | (7x-2)+(3x+8)=180 | | 12-6=30 |